2005
DOI: 10.1158/1078-0432.ccr-04-2207
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3σ Expression Is an Independent Prognostic Parameter for Poor Survival in Colorectal Carcinoma Patients

Abstract: Purpose: 14-3-3σ is an intracellular, dimeric, phosphoserine binding protein that is expressed in epithelial cells and involved in cancer development. In this study, we examined the expression of 14-3-3σ and evaluated its clinical significance in colorectal carcinoma. Experimental Design: Expression of 14-3-3σ was analyzed by Western blot in nine colorectal carcinoma cell lines, eight paired colorectal carcinoma tissues, and normal mucosas. Immunohistochemistry was used to evaluate expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
75
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 31 publications
9
75
2
Order By: Relevance
“…In these tumors, increased 14-3-3σ expression was correlated with hypomethylation of the CpG island. Similar findings have been reported for colorectal [19] and pancreatic cancers [35] and it has been postulated that 14-3-3σ over expression may be responsible for promoting proliferation and/or preventing apoptotic signal transduction [18]. Elevated 14-3-3σ expression has been reported as contributing to drug resistance in breast cancer cell lines [36], and its increased expression in the anaplastic cancer cell lines in the current study, may be able to explain, at least in part, the widespread resistance to chemo-therapeutic agents noted in this aggressive malignancy [37].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In these tumors, increased 14-3-3σ expression was correlated with hypomethylation of the CpG island. Similar findings have been reported for colorectal [19] and pancreatic cancers [35] and it has been postulated that 14-3-3σ over expression may be responsible for promoting proliferation and/or preventing apoptotic signal transduction [18]. Elevated 14-3-3σ expression has been reported as contributing to drug resistance in breast cancer cell lines [36], and its increased expression in the anaplastic cancer cell lines in the current study, may be able to explain, at least in part, the widespread resistance to chemo-therapeutic agents noted in this aggressive malignancy [37].…”
Section: Discussionsupporting
confidence: 87%
“…14-3-3σ expression has also been reported to be increased in head and neck squamous cell carcinomas [16] and pancreatic cancers by microarray and real-time PCR studies [17], when compared to corresponding normal tissues. Perathoner et al [18] also demonstrated strong 14-3-3σ expression by Western blot analysis in 4/8 colorectal carcinoma cell lines and 6/8 tumor tissue pairs. 14-3-3σ was also overexpressed by immunohistochemistry in 39% of colorectal carcinomas and appeared to be associated with a worse prognosis.…”
Section: Introductionmentioning
confidence: 88%
“…Inactivation of 14-3-3Û gene by CpG methylation and/or reduced expression of 14-3-3Û have been reported in a varity of human cancers, including ovarian (13,14), cervix (15), vulvar (16,17), corpus (18), lung (19), oral (20), liver (21), skin (22), breast (23,24), gastric (25,26), renal (27), testis (27) and colorectal (28). Association of 14-3-3Û with clinical outcome has been found in patients with endometrial carcinoma (18), ovarian carcinoma (14), breast carcinoma (24) and colorectal carcinoma (28).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of expression of 14-3-3σ expression has been observed in breast cancer 6 and ovarian, prostate, and endometrial cancer, 7 while being found in increased levels in colon cancer, 8 lung cancer 9 and pancreatic cancer. 10 A previous studies has demonstrated that 14-3-3σ functions as a tumor suppressor by exerting positive regulation on p53 activity resulting in inhibition of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…These different roles have also been demonstrated in a clinical setting. Decreased expression of 14-3-3σ has been associated with a poor prognosis in cholangiocarcinoma, 17 breast carcinoma, 18 and uterine serous carcinoma 19 whereas increased expression of 14-3-3σ in colon, 8 pancreatic, 10 and gastric 20 cancers has been associated with a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%